"But we are shying all of us away, from that thing" : the Coronavirus Pandemic and the crisis of teenage pregnancies in Kenya - Kipury, Siraiyion Soinda (Rhodes University, Faculty of Humanities, Department of History)
This thesis historicises the post-colonial discourse on teenage pregnancy in Kenya. The coronavirus pandemic lockdowns in 2020 led to an increase in sexual violence perpetrated largely against teenage girls, resulting in pregnancy. This crisis revealed that the current discourse has created silence around sex and rape. It therefore does not consider the circumstances surrounding the pregnancies of teenage girls and for that reason perpetuates stereotypes of them being poor, irresponsible, dropouts. It finds that these ideas materialise in the form of adolescent sexual and reproductive health legislation which has real effects on pregnant teenage girls. Through a lack of law and policy enforcement, the discourse legitimises itself in a cyclic fashion. It argues that understanding the way the discourse has perpetuated itself from the past into the present is key to transforming this legislation and therefore their experiences. It uses an Oral History methodology to centre the perspectives of women who had teenage pregnancies in the past, and uses their stories to develop an understanding of how the discourse functions. It identifies news media and legislation as two major sites of discourse, carrying out an analysis of the language and content exhibited to observe the way cultural stereotypes around teenage pregnancy are preserved and re-created. It draws parallels between past and present sexual and reproductive health laws (1963-2020) to demonstrate the longevity of gendered and misogynistic ideologies surrounding women's sexuality. It finds that language, blame/shame, and exclusion are the means through which the discourse has impressed itself upon Kenyan society throughout the post-colonial period. This thesis concludes that becoming aware of these means renders the discourse abnormal and unnatural, therefore creating the possibility of opening it up to change.
Keywords: Teenage pregnancy -- Kenya; Postcolonialism -- Kenya; Kenya -- History -- 1963-; Oral history -- Kenya; COVID-19 Pandemic, 2020-2023 -- Influence